2020
DOI: 10.3390/ijerph17062118
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Chromium Reducing Bacillus Cereus Species from Chromium-Contaminated Soil for the Biological Detoxification of Chromium

Abstract: Chromium contamination has been an increasing threat to the environment and to human health. Cr(VI) and Cr(III) are the most common states of chromium. However, compared with Cr(III), Cr(VI) is more toxic and more easily absorbed, therefore, it is more harmful to human beings. Thus, the conversion of toxic Cr(VI) into Cr(III) is an accepted strategy for chromium detoxification. Here, we isolated two Bacillus cereus strains with a high chromium tolerance and reduction ability, named B. cereus D and 332, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Bacteria capable of reducing Cr (VI) mainly belong to nitrate-reducing, Fe (III)-reducing, and sulphate-reducing bacteria. Among the gram positive bacteria, Bacillus, Deinococcus, and Arthrobacter have shown Cr (VI) reduction capability [107,150,151]. Meanwhile, Enterococcus, Shewanella, Pseudomonas, Escherichia, Thermus, and Ochrobactrum are examples of gram-negative bacteria with potential application in bioremediation [152][153][154][155][156][157].…”
Section: Bioreductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria capable of reducing Cr (VI) mainly belong to nitrate-reducing, Fe (III)-reducing, and sulphate-reducing bacteria. Among the gram positive bacteria, Bacillus, Deinococcus, and Arthrobacter have shown Cr (VI) reduction capability [107,150,151]. Meanwhile, Enterococcus, Shewanella, Pseudomonas, Escherichia, Thermus, and Ochrobactrum are examples of gram-negative bacteria with potential application in bioremediation [152][153][154][155][156][157].…”
Section: Bioreductionmentioning
confidence: 99%
“…The best-known disposal method of wastes and wastewaters enriched in chromium is often reduction of Cr (VI) to a less mobile and less toxic form, Cr (III), because Cr in industrial wastes occurs predominantly in the hexavalent form [ 27 ]. Some strategies used for chromium pollution remediation include chemical reduction methods by reducing agents such as Fe (0) and Fe (II), precipitation, adsorption, ion exchange, electrocoagulation, or biological reduction as a result of microbial metabolism [ 21 , 25 , 107 , 108 , 109 ].…”
Section: Remediation Strategiesmentioning
confidence: 99%
“…Physiological and biochemical analyses were performed according to the environmental engineering microorganism detection manual [ 41 , 42 ]. Gram staining experiments were performed, based on the method described by Li et al [ 43 ]. Physiological and biochemical characterizations including the Voges–Proskauer (VP), starch hydrolysis, glucose oxidative fermentation, gelatin hydrolysis, peroxidase, and contact oxidase tests were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Yan et al (2018) [ 10 ] reported the successful remediation of chromium-contaminated soil using an electric field to mobilize and extract contaminants, employing iron-loaded activated carbon electrodes in a three-dimensional system. Bioremediation approaches have also been explored for Cr-contaminated soil, with certain bacteria, such as Bacillus cereus, identified for their ability to reduce and detoxify Cr Li et al (2020) [ 11 ]. Phytoremediation, which involves using plants to remove contaminants from the soil, has been studied for Cr(VI) contamination.…”
Section: Introductionmentioning
confidence: 99%